A molecular epidemiological investigation of PEDV in China: Characterization of co‐infection and genetic diversity of S1‐based genes. Issue 3 (13th December 2019) - Su, Mingjun; Li, Chunqiu; Qi, Shanshan; Yang, Dan; Jiang, Ning; Yin, Baishuang; Guo, Donghua; Kong, Fanzhi; Yuan, Dongwei; Feng, Li; Sun, Dongbo
Abstract: Porcine epidemic diarrhoea virus (PEDV) is an emerging and re‐emerging epizootic virus of swine that causes substantial economic losses to the pig industry in China and other countries. The variations in the virus, and its co‐infections with other enteric viruses, have contributed to the poor control of PEDV infection. In the current study, a broad epidemiological investigation of PEDV was carried out in 22 provinces or municipalities of China during 2015–2018. The enteric viruses causing co‐infection with PEDV and the genetic diversity of the PEDV S1 gene were also analysed. The results indicated that, of the 543 diarrhoea samples, 66.85% (363/543) were positive for PEDV, and co‐infection rates of PEDV with 13 enteric viruses ranged from 3.58% (13/363) to 81.55% (296/363). Among these enteric viruses, the signs of diarrhoea induced by PEDV were potentially associated with co‐infections with porcine enterovirus 9/10 (PEV) and torque teno sus virus 2 (TTSuV‐2) ( p < .05). The 147 PEDV strains identified in our study belong to Chinese pandemic strains and exhibited genetic diversity. The virulence‐determining S1 proteins of PEDV pandemic strains were undergoing amino acid mutations, in which S58_S58insQGVN–N135dup–D158_I159del‐like mutations were common patterns (97.28%, 143/147). When compared with 2011–2014 PEDV strains, the amino acid mutations of PEDV pandemic strains were mainly located in the N‐terminal domain of S1 (S1‐NTD), and 21 novel mutations occurred in 2017 and 2018. Furthermore, protein homology modelling showed that the mutations in pattern of insertion and deletion mutations of the S1 protein of PEDV pandemic strains may have caused structural changes on the surface of the S1 protein. These data provide a better understanding of the co‐infection and genetic evolution of PEDV in China.